1970
DOI: 10.3758/bf03208640
|View full text |Cite
|
Sign up to set email alerts
|

The effect of multiple responses and certainty estimates on the integration of visual information

Abstract: was investigated in two experiments that employed a multiple-observation. tilt-discrimination task. The integration model of signal-detection theory generally overestimated the improvement in discrimination resulting from additional observations. Further. probabilistic multiple responses appeared detrimental to discrimination: These results differ from earlier findings using different discrimination tasks. Reasons for the differences were discussed in terms of within-trial redundance and interference causedby … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1971
1971
1974
1974

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The accurate predictions of the entire pattern of results in this study, and in two others (Doherty & Keeley, 1969;Keeley, Doherty, & Bach-man, 1970), is a convincing argument that the normative model is also an appropriate descriptive model, and provides evidence for the assumption of perceptual independence. The fine-grain predictions suggest that the use of a single index, such as d' (Halpern & Ulehla, 1970), provides a much less complete analysis of the perceptual and decision processes underlying an S's performance in multiple-observation studies.…”
Section: Resultsmentioning
confidence: 99%
“…The accurate predictions of the entire pattern of results in this study, and in two others (Doherty & Keeley, 1969;Keeley, Doherty, & Bach-man, 1970), is a convincing argument that the normative model is also an appropriate descriptive model, and provides evidence for the assumption of perceptual independence. The fine-grain predictions suggest that the use of a single index, such as d' (Halpern & Ulehla, 1970), provides a much less complete analysis of the perceptual and decision processes underlying an S's performance in multiple-observation studies.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Halpern and Ulehla (1970) showed that the tilt discrimination of highly visible lines was improved by sequential stimulus repetition. These findings are consistent with the small increase in the absolute judgment accuracy of brightness, observed in the present study.…”
Section: Stimulus Repetitionmentioning
confidence: 99%